Index of difficulty which is an Effective Factor on especial Skill Formation in Basketball Free Throw: Index of learning difficulty hypothesis - Talebi, Roohollah; Reza Taheri, Hamid; Sohrabi, Mahdi (Revista Publicando, 2018)
The purpose of this study is to examine the specific memory representation in special skill of Basketball Free Throw in distances (a “set shot”) except 4.5 m distance. It is aimed to examine the role of the Index of Difï¬culty (ID) in creating the specific memory in other distances except the distance of penalty shoots. Fifteen skilled basketball players (M age = 21.6 years, SD = 2.45 years) were chosen from sixty players; they performed 70 trials from 7 different distances on the first day (10 SHOTS from each distance toward the basket). The next day, each player performed 10 SHOTS from each distance, but this time, it was different in terms of the baskets”™ sizes and their quantities. The result of linear regression on trials score on the first day revealed the representation of special skill in penalty point and on the second day, representation of special skill was seen in 3 different distances from the ring (manipulated ring). These results indicate that Index of Difï¬culty protection can be a factor of private memory representation in distances except 4.5 m distance.